Från Motorväg till Sjöväg - En fallstudie om möjligheterna att starta upp linjetrafik för containers mellan Polen och Sverige - Olsson, Jonas; Büchel, Benjamin (My University, 2015)
Due to its low transportation price, the trailer has become the most used alternative for transportation of goods between Sweden and Poland. An increase of trailers on the Swedish roads leads to a higher traffic density, which affects the environment and the Swedish population in the form of high CO2 emissions and noise. This case study aims to investigate the possibility of implementing a route between Szczecin, Poland, and Gothenburg, Sweden, in order to transferring goods from the roads to the sea. This alternative would reduce the amount of green gas emissions, which is produced due to transportation with trailer. The idea is based on using containers of the 45’ PW-model instead of trailers. This type of container has the same dimensions as a trailer and accommodates as many EU pallets. The result that has been obtained from this report is that the possibility exists, however, the interest is relatively low since the current option is much cheaper and before this route is possible and functional there has to be a change in transportation price for the different kinds of transportation alternatives.
Keywords: Transportteknik och logistik; Transport; Transport Systems and Logistics; Transport